2004
DOI: 10.1074/jbc.m314114200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Dentin Matrix Protein-1 on Hydroxyapatite Formation Provide Insights into in Vivo Functions

Abstract: Dentin matrix protein-1 (DMP1) is a mineralized tissue matrix protein synthesized by osteoblasts, hypertrophic chondrocytes, and ameloblasts as well as odontoblasts. DMP1 is believed to have multiple in vivo functions, acting both as a signaling molecule and a regulator of biomineralization. Using a cell-free system in vitro, we evaluated the action of DMP1 in the regulation of hydroxylapatite (HA) formation and crystal growth. The non-phosphorylated recombinant protein acted as an HA nucleator, increasing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
146
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 174 publications
(170 citation statements)
references
References 38 publications
14
146
1
2
Order By: Relevance
“…At present, it is unclear whether the trace amounts of full-length DMP1 secreted into the ECM have a function(s) different from that of its processed fragments. Previous in vitro mineralization studies showed that full-length bovine DMP1 made by bone marrow stromal fibroblasts inhibits hydroxyapatite formation whereas the COOH-terminal fragment isolated from rat bone promotes formation of the apatite crystals [14]. Future in vivo studies are warranted to test the biological functions of the full-length form of DMP1 in comparison with those of its processed fragments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, it is unclear whether the trace amounts of full-length DMP1 secreted into the ECM have a function(s) different from that of its processed fragments. Previous in vitro mineralization studies showed that full-length bovine DMP1 made by bone marrow stromal fibroblasts inhibits hydroxyapatite formation whereas the COOH-terminal fragment isolated from rat bone promotes formation of the apatite crystals [14]. Future in vivo studies are warranted to test the biological functions of the full-length form of DMP1 in comparison with those of its processed fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the obvious differences in their biochemical features, it is logical to hypothesize that these variants may have distinct functions and play different roles in biomineralization. In vitro mineralization studies have demonstrated that the COOH-terminal fragment promotes mineralization by acting as a nucleator for hydroxyapatite formation [14][15][16]. Information regarding the biological functions of the NH 2 -terminal fragment and DMP1-PG is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that specific proteins were phosphorylated and dephosphorylated during the stages of initiation and proliferation of mineral crystals based on solution free studies of the effects of these proteins [2][3][4][5][6] and on our unpublished micro-array results showing upregulation of kinases during early stages of mineralization and down-regulation of phosphatases at the same time. We also hypothesized that the functions of the phosphatases was not simply to elevate the local inorganic phosphate concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In cell-free mineralization studies the ability of extracellular matrix phosphoproteins such as osteopontin (OPN) [1,2], bone sialoprotein (BSP) [3,4], dentin matrix protein-1 (DMP1) [5] and phosphophoryn [6] to initiate hydroxyapatite (HA) mineral deposition and regulate the rate and extent of growth of the HA crystals is dependent on their state of phosphorylation. While the importance of the phosphate ion for appropriate mineral deposition is well recognized [7], it is only in recent years that attention has been paid to whether or not the extracellular matrix proteins were phosphorylated, as well as to their extent of phosphorylation and the enzymes involved in these posttranslational modifications [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation